(untitled) (BIRDEM Medical Journal, 2024)
Background: Cardiovascular disease (CVD) is a major cause of death and disability among people with diabetes mellitus (DM). Hypoglycemia is a potential risk factor to augment life threatening CVD. This study intended to find out impact of severe hypoglycemia in adverse cardiovascular and neurological events among patients with DM. Methods: This cross-sectional study was conducted among diabetic patients with severe hypoglycemia (plasma glucose <70 mg/dl or 3.9 mmol/l) admitted in BIRDEM General Hospital from March 2014 to April 2015. Patients were categorized into two groups depending on blood glucose values (group A <2.8 and group B e”2.8) for analytical purpose. Major cardiac events including acute myocardial infarction (MI), non ST elevated MI or arrhythmia were observed along with neurological outcome including acute stroke, hypoglycemic encephalopathy and convulsion by both relevant clinical examinations and investigations as appropriate. Data were collected at discharge or death if any. Results: Among the 311 patients, 62% were in the age group of 51 to 60 years with mean age 49.02 years. Mean duration of DM was 8.5 (±5.4) years and in 85.5% cases HbA1c was e”7%. Majority was on insulin (79.41%); predominantly on premixed (33.5%) and self mixed (35.7%) regime. Meal related factors (p <0.001) e.g., delayed or missed meal, insulin related factors (p<0.001) e.g., miscalculation, overdosing were significant predisposing factors for developing hypoglycemia. Multivariate analysis revealed frequency of hypoglycemia was more in diabetic nephropathy (p<0.01), chronic liver disease (p=0.01), gastroparesis (p=0.01), cognitive impairment (p<0.001), established CVD (p=0.02) and adrenal insufficiency (p<0.01). Nocturnal hypoglycemia (33.80% ) and hypoglycemic unawareness (44.23%) was also observed among the participants. Cardiovascular events were found in 98 (31.55%) individuals which included any form of arrhythmia (p=0.02), non ST elevated MI (p=0.08) and ST elevated MI (p<0.008). Among the neurological events (n=67, 21.54%), hypoglycemic encephalopathy (p<0.02) and acute stroke (p=0.01) were significant. Seizure happened in 15 individuals (p=0.53). Nine patients died (death rate 2.89%). Predominant cause of death was acute MI (6, 66%) and hypoglycemic encephalopathy (3, 33.33%). Conclusion: The major finding of this study suggest that severe hypoglycemia is strongly associated with fatal cardiovascular and neurological events including MI, acute stroke and hypoglycemic encephalopathy in diabetic patients predominantly treated with insulin. Mortality was found in 2.89% participants. Co morbidities including renal disease, liver disease, gastroparesis, cognitive impairment increased the vulnerability of developing severe hypoglycemia. In most of the cases, lifestyle factors are the precipitating causes of hypoglycemia, which are readily recognizable and easily modifiable. Therefore, appropriate diabetic education and periodic reevaluation of patient’s knowledge, attitude and practice towards hypoglycemia is of utmost importance to prevent this common but life-threatening complication. BIRDEM Med J 2024; 14(3): 118-123